Cognitive-behavioural therapy combined with music therapy for chronic fatigue following Epstein-Barr virus infection in adolescents: a randomised controlled trial - Tarjei Tørre Asprusten; Eva Skovlund; Vegard Bruun Wyller; Maria Pedersen; Sadaf Malik; Julie Mangersnes; Gro Trondalen; Betty van Roy (BMJ Publishing Group, 2020)
Background Cognitive-behavioural therapy (CBT) is effective in chronic fatigue (CF) syndrome. However, CBT has not been investigated in postinfectious CF, nor is it known whether addition of therapeutic elements from other disciplines might be useful. We explored combined CBT and music therapy intervention for CF following Epstein-Barr virus (EBV) infection in adolescents.Methods Adolescents (12-20 years old) participating in a postinfectious cohort study who developed CF 6 months after an acute EBV infection were eligible for the present study. A combined CBT and music therapy programme (10 therapy sessions and related homework) was compared with care as usual in a randomised controlled design. Therapists and participants were blinded to outcome evaluation. Endpoints included physical activity (steps/day), symptom scores, recovery rate and possible harmful effects, but the study was underpowered regarding efficacy. Total follow-up time was 15 months. Power analyses suggested that 120 participants would be needed in order to detect a moderate effect size.Results A total of 91 individuals with postinfectious CF were eligible, and a total of 43 were included (21 intervention group, 22 control group). Concern regarding school absence due to therapy sessions was the main reason for declining participation. Seven individuals left the study during the first 3 months, leaving 15 in the intervention group and 21 in the control group at 3 months follow-up. No harmful effects were recorded, and compliance with appointment was high. In intention-to-treat analyses, the primary endpoint (number of steps/day) did not differ significantly between the intervention group and the control group (difference (95% CI) =-1298 (-4874 to 2278)). Secondary outcome measures were also not significantly different among the two groups.Conclusion An intervention study of combined CBT and music therapy in postinfectious CF is feasible. A fully powered trial is needed to evaluate efficacy; participants' concern regarding school absence should be properly addressed to secure recruitment.Trial registration number ClinicalTrials ID: NCT02499302, registered July 2015.